High-performance refractive index sensor for oil derivatives based on MWCNT photonic crystal microcavity. (June 2021) - Mahmoodi, Yaser; Fathi, Davood
Highlights: New all-optical oil derivatives RI sensor based on MWCNT 2D array was proposed. △ n = 0.1418 in 149 nm wavelength shift, so 1050 nm/RIU sensitivity was obtained. Un-reactive MWCNTs enable utilizing in high temperature / pressure environments. MWCNTs grown in AAO template give physically stable structure, even with defect. Abstract: In this paper, we propose a new all-optical sensor based on a two-dimensional (2D) regular array of multi-walled carbon nanotubes (MWCNTs) for the refractive index sensing of oil derivatives, for the first time. The interaction of optical wave with the desirable oil derivatives is enhanced using the slow light effect that makes the group velocity go down. We consider the geometric feature for the proposed sensor structure as a photonic crystal (PhC) with a line defect formed by missing some rows of MWCNT elements. The difference of refractive index △ n = 0.1418 between Butanol (C4 H10 O) and Nitrobenzene (C6 H5 NO2 ) host materials results in a wavelength shift of 149 nm, and indicates a sensitivity of 1050 nm/RIU, which can be widely used for the bio/chemical detection and environmental monitoring. To achieve the physical stability of the proposed sensor, MWCNTs are considered to be grown in the AAO (Al2 O3 ) template. By removing one or two rows of the MWCNTs and creating a linear defect within the sensor structure, whereas oil derivatives are injected into the defect area. We have achieved a sensitivity up to 870 nm/RIU. This proposed sensor with un-reactive structure of MWCNTs can be used in environments with high temperature and pressure such as oil refinery industry and other chemical processes industries under wide range of different reaction conditions.